Albinism in the Ancient Mediterranean World - John L. Hilton (Journal for the Study of Religion)
The discovery of DNA in the 20th century and recent biomedical research into the human genome in Southern Africa have shed much light on the diag-nostic, epidemiological, and sociological aspects of albinism. Less attention has been given to the historical evidence for the condition and its religious context, especially in the ancient Mediterranean World. This article assem-bles the meagre evidence for albinism in antiquity and investigates to what extent it was treated as ‘sacred’.